Forced and Illegal Migrations from the Western Balkans to Europe: An Applied Anthropology of Security Approach - Pangerc, Desirée (Bałkany Zachodnie w systemie bezpieczeństwa euroatlantyckiego, Bałkany XX/XXI, t. 7, 2015)
This article is devoted to the problems of globalization and migration. Especially from the 90s thenceforth, we have been observing a continuous increase of two criminal phenomena linked to forced and illegal migrations: smuggling of migrants and human trafficking.